When to replicate systematic reviews of interventions: consensus checklist. (15th September 2020) - Tugwell, Peter; Welch, Vivian Andrea; Karunananthan, Sathya; Maxwell, Lara J; Akl, Elie A; Avey, Marc T; Bhutta, Zulfiqar A; Brouwers, Melissa C; Clark, Jocalyn P; Cook, Sophie; Cuervo, Luis Gabriel; Curran, Janet Agnes; et al.
Abstract : Replication is an essential part of the scientific method, yet replication of systematic reviews is too often overlooked, and done unnecessarily or poorly. Excessive replication (doing the same study repeatedly) is unethical and a cause of research wastage. This article provides consensus based guidance on when to replicate and not replicate systematic reviews.